2015
DOI: 10.1155/2015/136810
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Expression of DNA Double-Strand Breaks Related Genes, ATM and GammaH2AX, in Thyroid Carcinoma

Abstract: ATM and γH2AX play a vital role in the detection of DNA double-strand breaks (DSB) and DNA damage response (DDR). This study aims to investigate ATM and γH2AX expression in thyroid cancer and discuss possible relationship between thyroid function tests and DNA damage. The expression of ATM and γH2AX was detected by immunohistochemistry in 30 cases of benign nodular goiter, 110 cases of well differentiated thyroid cancer, 22 cases of poorly differentiated thyroid cancer, and 21 cases of anaplastic thyroid cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
(39 reference statements)
1
10
0
Order By: Relevance
“…Increased γH2AFX expression may result in increased radiosensitivity ( 28 ). Multiple studies have revealed that γH2AFX expression is increased in certain types of cancer and their premalignant lesions ( 8 , 22 , 29 , 30 ), which supports the results of the present study. Overexpression of γH2AFX may represent an independent prognostic indicator of a poor overall patient survival rate ( 31 , 32 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Increased γH2AFX expression may result in increased radiosensitivity ( 28 ). Multiple studies have revealed that γH2AFX expression is increased in certain types of cancer and their premalignant lesions ( 8 , 22 , 29 , 30 ), which supports the results of the present study. Overexpression of γH2AFX may represent an independent prognostic indicator of a poor overall patient survival rate ( 31 , 32 ).…”
Section: Discussionsupporting
confidence: 92%
“…Tumorigenic events that occur early in the progression of major types of human cancer activate ATM-regulated cell cycle checkpoints and thereby an inducible barrier that inhibits tumor progression and genetic instability ( 7 , 24 ). A previous study has demonstrated that ATM expression was increased in certain types of cancer tissue compared with that in benign tumorous lesions and normal tissues ( 22 ). Other previous studies have suggested that ATM potentially represents a promising indicator for hyperplasia and cancer, and may serve as a useful marker for identifying patients with poor prognosis ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, gH2AX was found to play a role in the differentiation status of thyroid cancer. 69…”
Section: Resultsmentioning
confidence: 99%
“…Ataxia-telangiectasia mutated (ATM) is newly discovered gene that can initiate the repair of DNA double-strand breaks, and the expression level of ATM is closely correlated with the repair of damaged cells and the regulation of apoptosis cycle ( 5 ). Studies have shown that ( 6 8 ) abnormal expression of ATM plays pivotal roles in the occurrence of lung cancer, breast cancer, thyroid cancer and other types of cancers by regulating gene expression and angiogenesis. In addition, abnormal cell apoptosis is also a cause of the development and progression of tumor.…”
Section: Discussionmentioning
confidence: 99%